2021
DOI: 10.3390/dj9040037
|View full text |Cite
|
Sign up to set email alerts
|

Maintenance of Dental Records and Forensic Odontology Awareness: A Survey of Croatian Dentists with Implications for Dental Education

Abstract: Forensic odontology is the application of dentistry within the criminal justice system. Forensic expertise, including dental identification, mostly relies on dental records. We explored the practice of maintaining dental records among Croatian dentists, as well as their knowledge of legal regulations and the application of dental records in forensic odontology. In all, 145 dentists participated in an online survey. Questions covered general information on dentists, maintenance of dental records, and knowledge … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
9
1
3

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 14 publications
3
9
1
3
Order By: Relevance
“…However, more than one-third of subjects in the study were not familiar with the term 'forensic odontology' which is an area of concern. These findings of the present study differ from another study conducted recently on Croatian dentists (11).…”
Section: Discussioncontrasting
confidence: 99%
“…However, more than one-third of subjects in the study were not familiar with the term 'forensic odontology' which is an area of concern. These findings of the present study differ from another study conducted recently on Croatian dentists (11).…”
Section: Discussioncontrasting
confidence: 99%
“…Our study showed that dentists and students are quite satisfied with “Pedodontics”, which is consistent with the results of a study from Saudi Arabia 17 . Despite the satisfactory overall result, satisfaction with the knowledge and skills from “Dental behaviour management of children” is relatively low.…”
Section: Discussionsupporting
confidence: 89%
“…Our study showed that dentists and students are quite satisfied with "Pedodontics", which is consistent with the results of a study from Saudi Arabia. 17 Despite the satisfactory overall result, satisfaction with the knowledge and skills from "Dental behaviour management of children" is relatively low. Also, studies from the United States show that only 50%-60% of newly graduated dentists implemented the successful "tell-show-do" behaviour control technique.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As the incidence of caries decreases in more developed countries, the anomalies of dental diagnoses will increase even more. [7]…”
Section: Defining the Problemmentioning
confidence: 99%